PERAN PROGRAM CLUB BAHASA ARAB SEBAGAI MEDIA PENGEMBANGAN KOMPETENSI MAHARAH LUGHAWIYAH DI PONDOK PESANTREN DARUNNAJAH JAKARTA - Ikmal Maeliny; Arya Eka Saputra; Irwakhi Kholishotul Azam; Abyan Hanif Kurniawan; Muasomah Muasomah (Fakultas Teknik Universitas Negeri Makassar, 2026)
This research examines the role of the Arabic Language Club program in developing students' linguistic skills (maharah lughawiyah) at Pondok Pesantren Darunnajah Jakarta. Specifically, this study describes how the program is implemented and its impact on four language skills: speaking (kalam), listening (istima'), reading (qira'ah), and writing (kitabah), as well as the factors that support and hinder the program's implementation. Using a descriptive qualitative method, data were collected through participatory observation, in-depth interviews with coordinators and participants, and analysis of program documentation. Findings reveal that the Arabic Language Club, which has been actively operating since December 18, 2009, has successfully organized its activities in a systematic daily, weekly, monthly, and annual cycle. Among the four language skills, speaking ability (kalam) shows the most notable progress, followed by improved reading skills and expanded vocabulary mastery. The supportive atmosphere of the Islamic boarding school, diverse teaching approaches, and the dedication of coordinators are key factors in the program's success. Conversely, low self-confidence among students and limited vocabulary remain challenges that require ongoing, creative intervention.